2023
DOI: 10.1039/d3ja00130j
|View full text |Cite
|
Sign up to set email alerts
|

Catching up on calibration-free LIBS

Abstract: This review paper will present and critically discuss the evolution of the Calibration-Free LIBS (CF-LIBS) method and some of its new applications that appeared since the last extensive review on...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 147 publications
0
2
0
Order By: Relevance
“…Different calibration techniques are not discussed in detail in this review but can be found in the literature [77][78][79][80][81][82][83][84]. Spectral processing and data handling are, similarly, covered in detail elsewhere [85][86][87].…”
Section: Calibration Techniques and Spectral Treatment (Chemometrics)mentioning
confidence: 99%
“…Different calibration techniques are not discussed in detail in this review but can be found in the literature [77][78][79][80][81][82][83][84]. Spectral processing and data handling are, similarly, covered in detail elsewhere [85][86][87].…”
Section: Calibration Techniques and Spectral Treatment (Chemometrics)mentioning
confidence: 99%
“…To mitigate these problems, several adaptations of CF-LIBS have been proposed [103]. Recent review publications [104,105] provide a detailed discussion of foundational concepts, their influencing factors, analytical efficacy, and potential measurement uncertainties.…”
Section: Classic and Calibration-free Libsmentioning
confidence: 99%
“…An interesting variant of CF-LIBS worth mentioning is the one-point calibration method. Using only one calibration point, it introduces an empirical correction to the purely theoretical CF-LIBS approach, helping to determine essential experimental and spectroscopic parameters, which are normally not easy to obtain [104].…”
Section: Classic and Calibration-free Libsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of the LIBS technique to benchmark silicon levels in samples at a high throughput made it an ideal screening tool, although traditional LIBS’ reliance on matrix-matched standards generated a unique challenge for environmental sample quantification. While a calibration free – LIBS approach, 28,29 or the one-point calibration LIBS approach, 29 could be used to circumvent the need for a matrix matched calibration, these techniques require a time-resolved spectrometer which was not available for this work. SEM–EDS provided high-spatial resolution mapping capabilities and the ability to do semiquantitative analysis to better understand surface-level silicon concentration and the structure of the phytoliths in the plant tissues.…”
Section: Introductionmentioning
confidence: 99%